THE INFLUENCE OF DIGITAL MARKETING, PRODUCT QUALITY, SERVICE QUALITY AND PRICE PERCEPTION TOWARD PURCHASE DECISION: (Survey at Lady Fame Store Bandar Lampung ) - Kartika, Aulia; Aplilani, deddy; Adistya, Diang (Jurnal Kompetitif Bisnis, 2023)
The purpose of this study is to determine and explain the influence of digital marketing, product quality, service quality, and price perception toward customer’s purchase decision at LadyFame in Bandar Lampung. This research category is belonged to explanatory research with quantitative method. Purposive sampling was used to get a valid data with 100 Ladyfame Store consumers as the respondent using Likert Scale. SPSS Version 20.0 was used to analayzed the data. Based on the result, this research shows all the variables that consist of digital marketing, product quality, service quality, and price perception simultaneously have positive influence toward purchase decision but in a low number with R Square 0.109. Partially only product quality that have positive influence with t-value 3.309 > t table, meanwhile the other variable have no influence toward purchase decision on LadyFame Bandar Lampung.